A Literature Review: The Effectiveness of Using Kahoot! to Enhance Student’s Vocabulary - Rahayu, Tantiana Dewi; Ailia, Nia; Junita, Fera; Ifana, Nur (Universitas Negeri Medan, 2024)
This study aimed to analyze the effectiveness of using Kahoot! to enhance student’s vocabulary. This article used qualitative research which presents the results of a literature review on the effect of using Kahoot! for learning specifically to enhance student’s vocabulary includes 15 studies. The findings showed that the use of Kahoot! as a digital tool is effective in improving the English vocabulary. The students had positive attitudes towards Kahoot! being used in the classroom because it was fun and led them to enjoy the lessons. In addition, student experienced a significant vocabulary enhancement with the use of the Kahoot! Application. Teachers must be trained to apply and incorporate technology. Keywoords: Student’s vocabulary, Kahoot!, Media learning, ICT